Seroprevalences and Correlates of Hepatitis B and C Among Cameroonian Pregnant Women - Florent Ymele Fouelifack; Jeanne Hortence Fouedjio; Jovanny Tsuala Fouogue; Loic Dongmo Fouelifa (Clinical Medicine Insights: Reproductive Health, 2018)
Background and rationale: Viral hepatitis B (VHB) and viral hepatitis C (VHC) are major public health issues in resource-poor countries where vertical transmission remains high. Aim: To assess prevalences and correlates of VHB and VHC among women attending antenatal clinic. Methods: A cross-sectional study at the Yaounde Central Hospital from January 1 to June 30, 2016. We included 360 pregnant women who were screened for hepatitis B virus surface antigen (HbsAg) and VHCAb by rapid diagnostic test (DiaSpot Diagnostics, USA) followed by confirmation of positive results by a reference laboratory. Odds ratios (95% confidence interval [CI]) were used to measure associations between variables. Statistical significance was set for P -value <.05. Results: Mean age was 27.9 ± 5.6 years. The prevalences of HbsAg and VHCAb were 9.4% (n = 34) and 1.7% (n = 6), respectively. Multiplicity of sex partners was significantly associated with HbsAg positivity (adjusted odds ratio [aOR]: 11.6; 95% CI: 5.1-26.7; P  < .001) while none of the studied factors was associated with VHCAb. Conclusion: The high prevalence of hepatitis B among pregnant women supports systematic screening and free vaccination of pregnant women and women of childbearing age.